Morphological and Molecular Data of a Padina (Dictyotaceae) Seaweed Sample Collected from Ly Son Island, Quang Ngai Province - Phong, Vu Dinh; Ngoc, Nguyen Thi Bich; Hue, Huynh Thi Thu; Thanh, Le Tat (VNU Journal of Science: Natural Sciences and Technology, 2026)
The genus Padina (Dictyotales, Phaeophyceae) belongs to the group of brown algae (Phaeophyceae) and is widely distributed across marine regions worldwide, particularly abundant in tropical and subtropical areas of the Western Pacific. Padina species are notable sources of bioactive compounds. According to algal taxonomic databases, 95 species have been reported within this genus, of which 59 are currently taxonomically accepted. Species of the genus Padina have long been utilized as food due to their nutritional content, including proteins, carbohydrates, lipids, vitamins, carotenoids, and minerals. In addition, several Padina species are used in pharmaceutical applications, health supplements, and cosmetic products. They also play a vital ecological role in marine ecosystems. However, Padina species exhibit highly similar morphological characteristics, making taxonomic identification based solely on morphology challenging. While morphological methods remain widely used in seaweed taxonomy, they have inherent limitations. In Vietnam, in-depth taxonomic studies employing genetic data or integrative approaches combining molecular and morphological analyses for this genus remain scarce. To address this knowledge gap, this study collected a Padina sample (code: LS1) from Ly Son Island, Quang Ngai Province, and applied an integrative taxonomic approach combining morphological examination with chloroplast rbcL gene sequencing to identify the species and elucidate its phylogenetic relationships within the genus Padina . Morphological analysis of sample LS1 indicated strong similarity to Padina tetrastromatica based on existing identification keys for the genus. Molecular analysis of the rbcL region supported this identification, with LS1 clustering closely with Padina tetrastromatica , supported by high bootstrap values (MLBS = 95%, BPP = 97%). The interspecific genetic divergence among Padina species ranged from 0.2% to 7.4%, with an average of 4.5%. The results of both morphological and molecular phylogenetic analyses confirmed that the sample collected from Ly Son Island belongs to Padina tetrastromatica . This concordance between traditional taxonomy and molecular biology underscores the reliability of the integrative approach. The findings not only enhance our understanding of Padina biodiversity in the region but also pave the way for further studies exploring the biological potential of this species.